IFPA meeting 2016 workshop report III: Decidua-trophoblast interactions; trophoblast implantation and invasion; immunology at the maternal-fetal interface; placental inflammation. (December 2017) - Aplin, John D.; Beristain, Alexander; DaSilva-Arnold, Sonia; Dunk, Caroline; Duzyj, Christina; Golos, Thaddeus G.; Kemmerling, Ulrike; Knöfler, Martin; Mitchell, Murray D.; Olson, David M.; Petroff, Margaret; Pollheimer, Jürgen; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialised topics. At IFPA meeting 2016 there were twelve themed workshops, four of which are summarized in this report. These workshops related to various aspects of placental biology but collectively covered areas of decidual-trophoblast interaction, regulation of trophoblast invasion, immune cells at the maternal-fetal interface, and placental inflammation.